2005
DOI: 10.1371/journal.pmed.0020313
|View full text |Cite|
|
Sign up to set email alerts
|

Oncogenic Transformation by Inhibitor-Sensitive and -Resistant EGFR Mutants

Abstract: BackgroundSomatic mutations in the kinase domain of the epidermal growth factor receptor tyrosine kinase gene EGFR are common in lung adenocarcinoma. The presence of mutations correlates with tumor sensitivity to the EGFR inhibitors erlotinib and gefitinib, but the transforming potential of specific mutations and their relationship to drug sensitivity have not been described.Methods and FindingsHere, we demonstrate that EGFR active site mutants are oncogenic. Mutant EGFR can transform both fibroblasts and lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
515
0
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 618 publications
(540 citation statements)
references
References 33 publications
18
515
0
7
Order By: Relevance
“…Jiang et al (2005) recently reported a similar observation for just the G695S and L834R EGFR mutants in Ba/F3 cells. Moreover, Greulich et al (2005) found that several of the EGFR mutants studied here can transform NIH 3T3 cells. Thus, from our own studies and those published recently by other groups Jiang et al, 2005;Chen et al, 2006;Sakai et al, 2006), it appears that the EGFR mutations identified in gefitinibresponsive lung cancer patients are oncogenic.…”
Section: Gefitinib-sensitizing Mutations Enhance Basal Egfr Autophospmentioning
confidence: 66%
“…Jiang et al (2005) recently reported a similar observation for just the G695S and L834R EGFR mutants in Ba/F3 cells. Moreover, Greulich et al (2005) found that several of the EGFR mutants studied here can transform NIH 3T3 cells. Thus, from our own studies and those published recently by other groups Jiang et al, 2005;Chen et al, 2006;Sakai et al, 2006), it appears that the EGFR mutations identified in gefitinibresponsive lung cancer patients are oncogenic.…”
Section: Gefitinib-sensitizing Mutations Enhance Basal Egfr Autophospmentioning
confidence: 66%
“…[67][68][69][70][71] However, insertion mutations of exon 20, D770_N771 (insNPG), D770_N771 (insSVQ), D770_N771 (insG), and point mutations in exon 20 (V769L, N771T) were associated with EGFR TKI resistance. 12,195 This observation has been confirmed in an in vitro model in which insertion mutations in exon 20 rendered transformed cells less responsive to EGFR TKIs Figure 7 Suggested algorithm for molecular testing for patients with lung adenocarcinoma. The algorithm defines the rationale in selecting patients who could benefit from EGFR and EML4-ALKA targeted therapy.…”
Section: Primary Resistance To Egfr Targeted Therapymentioning
confidence: 84%
“…Exons 18-21 in the tyrosine kinase region of the EGFR gene are scaled up; a detailed list of EGFR mutations in these exons associated with sensitivity (green) or resistance (orange) to EGFR TKI. 6,12,[67][68][69][70][71][80][81][82][83][84]195 The frequency of the mutations is labeled to the side of the color-coded bars. The most prevalent EGFR mutations are in-frame deletions of exon 19 (45%), followed by L858R substitution in exon 21 (41%).…”
Section: Egfr Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soft agar assays were carried out in triplicate as previously described 15, 16. Photographed images of soft agar colonies taken after 2–3 weeks were quantified using Image J software (NIH).…”
Section: Methodsmentioning
confidence: 99%